UHC in Africa : A Framework for Action - World Bank (World Bank, Washington, DC, 2017)
Many countries in Africa still contend with high levels of child and maternal mortality, malnutrition is far too common, and most health systems are not able to deal effectively with epidemics and the growing burden of chronic diseases. These challenges call for renewed commitments and accelerated progress toward Universal Health Coverage (UHC). Besides the moral argument that it is not acceptable that some members of society should face death, disability, ill health or impoverishment for reasons that could be addressed at limited cost, UHC is a good investment. Prevention of malnutrition and ill health is likely to have enormous benefits in terms of longer and more productive lives, higher earnings, and averted care costs. Effectively meeting demand for family planning will accelerate the fertility transition, which in turn will result in higher rates of economic growth and more rapid poverty reduction. And strong health and disease surveillance systems halt epidemics that take lives and disrupt economies.